Status of water security in inland South African cities - Thokozani Simelane; Claudious Chikozho; Shingirirai Sevious Mutanga; Lavhelesani Rodney Managa; Fhulufelo Tshililo; Thandeka Dabata (Journal of Digital Food, Energy & Water Systems)
Most cities in South Africa are in dire need of water security. Intervention measures to reduce the risk of water shortages now and the near future are urgently needed. This can possibly be attained through the diversification of water sources and the application of smart or digital technologies to reduce water wastage.  Meaning that, cities which are at risk of water scarcity may consider a variety of alternative means, which includes smart technologies and efficient use of recycled water to meet the ever-increasing demand.  In this study the status of water security and sanitation in two inland cities (i.e. Mbombela (Nelspruit) and Polokwane (Pietersburg)) was investigated.  A gap between supply and demand for water to households was found to be large. The primary demand for water derives from households that are connected to the municipal reticulation system and used for drinking and sanitation.  Water security concerns were found to be from households in need of water supply and unmeasured demands from informal settlements that are illegally connected to the system. The uncertain nature of water availability due to climate change meant that the risk of water insecurity in studied cities was high. To ameliorate this, municipalities need to adopt new ways of managing water.  This may include the use of digital technologies and the promotion of harvesting rainwater as an alternative source.  Maintenance of existing infrastructure is highly recommended to improve efficiencies in water usage.  Overall, results reflect the high risk of water security in Mbombela and Polokwane. Of great concern is the need to manage water to improve the efficiency of its use to meet the ever-increasing demand.